Emodin promotes GSK-3β-mediated PD-L1 proteasomal degradation and enhances anti-tumor immunity in hepatocellular carcinoma - Xuemei Yang; Weiguang Chen; Haitao Sun; Weicong Chen; Wei Xu; Chunyu He; Yang Liu; Ying Kuang; Yanhao Ma; Binglian Zhong; Chaojie Li; Guohuan Li; et al. (Chinese Medicine)
Abstract Background Programmed death-ligand 1 (PD-L1), a prominent immune checkpoint, interacts with programmed death protein-1 (PD-1) on cytotoxic T cells within tumors and promotes immune evasion. Emodin, which is known to destabilize PD-L1 in breast cancer, has great potential for enhancing anti-tumor immunity. However, whether emodin can modulate PD-L1 levels in hepatocellular carcinoma (HCC) and enhance anti-tumor immune response remains unclear. Materials and methods PD-L1 levels were assessed by western blot and RT-qPCR, the degradation mechanism was analyzed using specific inhibitors. Network pharmacology, molecular docking, and glycogen synthase kinase-3 beta (GSK-3β) modulation analyzes were performed to validate emodin’s target. In vivo anti-tumor effects were evaluated in H22 subcutaneous tumor model, and CD8+ T cells and RNA-seq data were analyzed. The synergistic effects of emodin and an anti-PD-L1 antibody were assessed. Results Emodin effectively reduced PD-L1 levels in H22 cells and increased anti-tumor activity in an H22 subcutaneous tumor model by promoting CD8+ T cells infiltration and TNF-α, IFN-γ, and granzyme B secretion. Mechanistically, emodin accelerated PD-L1 degradation through the proteasome pathway in both mouse and human HCC cell lines, as confirmed by the use of proteasome, lysosome and autophagy inhibitors. Network pharmacology analysis and molecular docking revealed that GSK-3β, a key regulator of PD-L1 degradation, is a target of emodin. Selective inhibitor-mediated suppression of GSK-3β largely reversed the regulatory effect of emodin on PD-L1. In contrast, overexpression of GSK-3β with a plasmid decreased PD-L1 protein levels and augmented emodin’s effect on PD-L1. Additionally, RNA-sequencing revealed the role of emodin in improving the immune responses in the tumor microenvironment. Finally, we observed a synergistic effect when the H22 cell subcutaneous tumor model was treated with emodin and anti-PD-L1 antibody. Conclusion Emodin exerts anti-tumor effects by promoting GSK-3β-mediated PD-L1 proteasomal degradation and enhancing the anti-tumor effects of CD8+ T cells, indicating that emodin may be a promising therapeutic option for HCC. Graphical Abstract